Effects of variable magma supply on mid‐ocean ridge eruptions: Constraints from mapped lava flow fields along the Galápagos Spreading Center - Alice Colman; John M. Sinton; Scott M. White; J. Timothy McClinton; Julie A. Bowles; Kenna H. Rubin; Mark D. Behn; Buffy Cushman; Deborah E. Eason; Tracy K. P. Gregg; Karl Grönvold; Silvana Hidalgo; et al. (Geochemistry, Geophysics, Geosystems)
Mapping and sampling of 18 eruptive units in two study areas along the Galápagos Spreading Center (GSC) provide insight into how magma supply affects mid‐ocean ridge (MOR) volcanic eruptions. The two study areas have similar spreading rates (53 versus 55 mm/yr), but differ by 30% in the time‐averaged rate of magma supply (0.3 × 106 versus 0.4 × 106 m3/yr/km). Detailed geologic maps of each study area incorporate observations of flow contacts and sediment thickness, in addition to sample petrology, geomagnetic paleointensity, and inferences from high‐resolution bathymetry data. At the lower‐magma‐supply study area, eruptions typically produce irregularly shaped clusters of pillow mounds with total eruptive volumes ranging from 0.09 to 1.3 km3. At the higher‐magma‐supply study area, lava morphologies characteristic of higher effusion rates are more common, eruptions typically occur along elongated fissures, and eruptive volumes are an order of magnitude smaller (0.002–0.13 km3). At this site, glass MgO contents (2.7–8.4 wt. %) and corresponding liquidus temperatures are lower on average, and more variable, than those at the lower‐magma‐supply study area (6.2–9.1 wt. % MgO). The differences in eruptive volume, lava temperature, morphology, and inferred eruption rates observed between the two areas along the GSC are similar to those that have previously been related to variable spreading rates on the global MOR system. Importantly, the documentation of multiple sequences of eruptions at each study area, representing hundreds to thousands of years, provides constraints on the variability in eruptive style at a given magma supply and spreading rate.